Association of metabolic syndrome components and their combinations with functional disability among older adults in a longevity-associated ethnic minority region of Southwest China - Haiyan Lu; Wenjie Liang; Hongyuan Huang; Kaiyong Huang; Lirong Zeng; Li Yang (Frontiers in Public Health)
PurposeMetabolic syndrome (MetS) is associated with functional disability; however, the associations between combinations of MetS components and functional disabilities remain largely unexplored.MethodsThis cross-sectional study was conducted among adults aged ≥60 years in Donglan County. Basic activities of daily living (ADL) disability and instrumental activities of daily living (IADL) disability were identified using physical self-maintenance and IADL scales. Modified Poisson regression and restricted cubic splines were used to evaluate the associations of MetS, the number of MetS components, and combinations of MetS components with functional disability.ResultsA total of 4,450 participants were enrolled in this study. Abdominal obesity was associated with a 1.03-fold (95% CI: 1.01–1.05) higher ADL disability risk. Lower HDL cholesterol remained associated with a 4% reduced risk of IADL disability (PR = 0.96, 95% CI: 0.93–0.99). The combination of abdominal obesity, elevated blood pressure, and elevated fasting glucose was correlated with a 1.08-fold (95% CI: 1.01–1.14) higher risk of ADL disability and a 1.12-fold (95% CI: 1.05–1.19) higher risk of IADL disability.ConclusionLower HDL cholesterol levels may serve as a protective factor against IADL disability. The combination of abdominal obesity, elevated blood pressure, and elevated fasting glucose appears to represent the highest-risk combination for both ADL disability and IADL disability in the older adult population.